Oncocytic variant of central mucoepidermoid carcinoma: a rare case report - Lima-Verde, Maria Elisa Quezado; Ramos, Fabrício de Lamare; Nogueira, Cleto Dantas; Távora, Fábio Rocha Fernandes; Soares, Eduardo Costa Studart; Sousa, Fabrício Bitu; Mota, Mário Rogério Lima; Alves, Ana Paula Negreiros Nunes (Journal of Oral Diagnosis, 2021)
Mucoepidermoid carcinoma constitutes a heterogeneous lesion and may present histological variations that make the diagnosis challenging. This study aims to report a rare diagnosis of central oncocytic mucoepidermoid carcinoma (OMEC). A 45-year-old female patient, presenting a 10-year-old history of increase of volume in the left posterior mandible, with dental displacement and no clinical sign of mucosal involvement. A well- limited hypodense area was observed radiographically, with cortical bone thinning and a discrete area of solution of continuity. Histopathological analysis of incisional biopsy revealed a malignant neoplasia with glandular differentiation, presenting multiple cystic and ductiform spaces and a prominent component of large oncocytic cells, such as cells with squamous, basaloid, and mucous aspects. Histochemical and Immunohistochemical findings contributed to the diagnosis of OMEC. Tumor resection and mandibular reconstruction with microsurgical fibular graft were considered. However, the patient refused the treatment. This is the first report of OMEC with intraosseous occurrence.